Stamping Disability Analysis on Material SPC 270 E - Sri Anastasia Yudistirani; Kisman H. Mahmud; Ery Diniardi (Journal of Applied Sciences and Advanced Technology, 2021)
Good production results will be a benchmark for a company to compete in today's free market era. To improve good quality is determined by several factors, including: raw material factors, production processes, labor, the state of the engine or dies and the environment. Basically, the production results are not all good, because there are several factors that influence it, as noted above. To overcome this, a company sets a quality requirement because it is very useful for good and quality production results. In determining good quality, it is necessary to conduct a research on the raw material at the SPC 270 E foot step by means of the testing method that will be carried out. The testing methods carried out consist of: tensile testing, hardness testing, metallographic testing, chemical composition testing, and dye penetrant testing. From the results of the research that has been done, it can be seen that the thinning material has an average tensile strength of 307.41 N/mm2, the standard used by the company is 270 - 323 N/mm2 and is still in accordance with the tolerance value. Whereas the material with a lump has an average Vickers hardness value of 124.24 HV, the standard used by the company is 135 HV and still fits the tolerance value.